Phototherapy and optogenetic stimulation improve cognitive function in sleep-deprived mice - Na Li; Xuechun Li; Zhongdi Jiang; Xiafei Shi; Huancheng Wu; Yi Liu; Huijuan Yin; Hongli Chen (Journal of Innovative Optical Health Sciences, 2025)
The hippocampus is the brain structure that is responsible for the formation of learning memories. Sleep disorders leading to cognitive impairment are strongly associated with the hippocampus. Phototherapy offers a new physical therapy for the treatment of sleep disorders, with the advantages of being noninvasive and having few side effects. However, the mechanism by which phototherapy improves cognitive impairment caused by sleep disorders remains unclear. In this study, we used phototherapy combined with optogenetic technology to investigate the effect of noninvasive phototherapy on cognitive functions in sleep-deprived mice. Our results suggest that phototherapy might improve cognitive functions in sleep-deprived mice by modulating the hippocampus. Our study expands the research progress on noninvasive phototherapy for the treatment of sleep disorders.